Follow up of fetal outcome in cases of maternal phenylketonuria in Northern Ireland. Issue 2 (1st September 2002) - Magee, A C; Ryan, K; Moore, A; Trimble, E R
Abstract : Background: Maternal phenylketonuria (PKU) can result in multiple congenital anomalies. In Northern Ireland, the prevalence of PKU is relatively high at 1 in 4000. Objective: To assess the outcome of 39 pregnancies in 20 mothers. Results: Dietary control was established before conception in 17 pregnancies (44%). Five mothers with hyperphenylalaninaemia had 11 pregnancies. There were no congenital anomalies in this group, and all appear to be developing normally. Fifteen women with classical PKU had 28 pregnancies. One pregnancy ended in a first trimester miscarriage. Twelve out of 27 (44%) completed pregnancies produced babies with a congenital anomaly and/or developmental delay. Conclusions: Most problems occurred when dietary control was not established until after the 2nd trimester. As the cohort of young women with treated PKU is growing steadily, maternal PKU is going to become an even greater cause for concern.